Study on Greenhouse Gas Emissions in Rice-Chickpea Cropping System - Mamatha, Kurku (2017)
The Climate Food and Farming (CLIFF) Research Network is an international research network that helps to expand young researchers' knowledge and experience working on climate change mitigation in smallholder farming. CLIFF provides grants for selected doctoral students to work with CGIAR researchers affiliated with the Standard Assessment of Mitigation Potential and Livelihoods in Smallholder Systems (SAMPLES) project. This presentation is a Study on Greenhouse Gas Emissions in Rice-Chickpea Cropping System by Kurku Mamatha, a scientist with the International Crops Research Institute for the Semi-Arid Tropics (ICRiSAT).